FAKTOR-FAKTOR YANG MEMPENGARUHI EMPLOYEE PERFORMANCE MELALUIEMPLOYEE CREATIVITY SEBAGAI MEDIASI - NOVIA RAMADHANI; R WASISTO RUSWIDIONO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this study is to analyze the effect of Leader Encouragement in Creativity and Knowledge Sharing on Employee Performance through Employee Creativity at the Class I Non TPI Bekasi Immigration Office. This research uses descriptive and causal research, and uses purposive sampling techniques. Respondents in this study were 61 employees. Data collection used a questionnaire distribution method with measurements using a Likert scale. Data processing used the Structural Equation Modeling (SEM) analysis method. Based on the results of the analysis and hypothesis testing, this study shows that the variable Leader Creativity Encouragement does not affect Employee Performance, while other variables such as the variables Knowledge Sharing and Employee Creativity affect Employee Performance.